Implementation of Islamic Education in Families Based on Baiti Jannati - Wildan Mahmudin; Mada Sumringah Sari; Nadia Kurnia Fauziah; Supiana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Islamic education has a significant influence in the family environment, which will then influence the child's later life, especially when the child mixes, integrates, and socializes with society. Islamic values ​​​​instilled from parental upbringing or family education will be ingrained in the child's heart in practicing those values. The success of a family in implementing Islamic education instilled in all family members and more importantly children will determine the child's success in interacting more in the external environment, both the school environment and the community. The type of research used by the author is field research. While the qualitative research method is a study based on the philosophy of postpositivist. Through the implementation of Islamic education in families based on Baiti Jannati, the family will become a place filled with love, happiness, and blessings. Education provided to children at home will shape them into individuals with noble character, responsibility, and close to Allah SWT. Success in creating this Islamic family will bring great benefits not only to family members, but also to the surrounding community.